2021
DOI: 10.3390/ijms22189705
|View full text |Cite
|
Sign up to set email alerts
|

High Mutational Heterogeneity, and New Mutations in the Human Coagulation Factor V Gene. Future Perspectives for Factor V Deficiency Using Recombinant and Advanced Therapies

Abstract: Factor V is an essential clotting factor that plays a key role in the blood coagulation cascade on account of its procoagulant and anticoagulant activity. Eighty percent of circulating factor V is produced in the liver and the remaining 20% originates in the α-granules of platelets. In humans, the factor V gene is about 80 kb in size; it is located on chromosome 1q24.2, and its cDNA is 6914 bp in length. Furthermore, nearly 190 mutations have been reported in the gene. Factor V deficiency is an autosomal reces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 99 publications
0
14
0
Order By: Relevance
“…As far as the patient is concerned, a familiar segregation analysis indicated that her mother was heterozygous for the already described c.2218C>T, p.Arg740* mutation [ 23 ] with FV plasma levels at 63%, indicative of a mild phenotype, with no noteworthy clinical symptoms. Her father was heterozygous for the c.3279G>A, p.Trp1093* mutation [ 24 ] and presented with FV plasma levels of 21%, also associated with a mild phenotype without significant symptoms.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As far as the patient is concerned, a familiar segregation analysis indicated that her mother was heterozygous for the already described c.2218C>T, p.Arg740* mutation [ 23 ] with FV plasma levels at 63%, indicative of a mild phenotype, with no noteworthy clinical symptoms. Her father was heterozygous for the c.3279G>A, p.Trp1093* mutation [ 24 ] and presented with FV plasma levels of 21%, also associated with a mild phenotype without significant symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…This study proposes a new advanced gene editing-based therapy for the correction of a new mutation in the F5 gene (c.3279G>A, p.Trp1093*), previously described by our research group [ 24 ]. A specific CRISPR/Cas9 technology was developed to treat coagulopathies arising from this mutation, which is protected by a Spanish patent (Ref.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations